Toxic effects of methylated benzo[a]pyrenes in rat liver stem-like cells - Trilecová, Lenka; Krčková, Simona; Marvanová, Soňa; Pĕnčíková, Kateřina; Krčmář, Pavel; Neča, Jiří; Hulinková, Petra; Pálková, Lenka; Ciganek, Miroslav; Milcová, Alena; Topinka, Jan; Vondráček, Jan; et al. (Chemical research in toxicology, 2011)
The methylated benzo[a]pyrenes (MeBaPs) are present at significant levels in the environment, especially in the sediments contaminated by petrogenic PAHs. However, the existing data on their toxic effects in vitro and/or in vivo are still largely incomplete. Transcription factor AhR plays a key role in the metabolic activation of PAHs to genotoxic metabolites, but the AhR activation may also contribute to the tumor promoting effects of PAHs. In this study, the AhR-mediated activity of five selected MeBaP isomers was estimated in the DR-CALUX reporter gene assay performed in rat hepatoma cells. Detection of other effects, including induction of CYP1A1, CYP1B1, and AKR1C9 mRNAs, DNA adduct formation, production of reactive oxygen species, oxidation of deoxyguanosine, and cell cycle modulation and apoptosis, was performed in the rat liver epithelial WB-F344 cell line, a model of liver progenitor cells. We identified 1-MeBaP as the most potent inducer of AhR activation, stable DNA adduct formation, checkpoint kinase 1 and p53 phosphorylation, and apoptosis. These effects suggest that 1-MeBaP is a potent genotoxin eliciting a typical sequence of events ascribed to carcinogenic PAHs: induction of CYP1 enzymes, formation of high levels of DNA adducts, activation of DNA damage responses (including p53 phosphorylation), and cell death. In contrast, 10-MeBaP, representing BaP isomers substituted with the methyl group in the angular ring, elicited only low levels DNA adduct formation and apoptosis. Other MeBaPs under study also elicited strong apoptotic responses associated with DNA adduct formation as the prevalent mode of toxic action of these compounds in liver cells. MeBaPs induced a weak production of ROS, which did not lead to significant oxidative DNA damage. Importantly, 1-MeBaP and 3-MeBaP were found to be potent AhR agonists, one order of magnitude more potent than BaP, thus suggesting that the AhR-dependent modulations of gene expression, deregulation of cell survival mechanisms, and further nongenotoxic effects associated with AhR activation may further contribute to their tumor promotion and carcinogenicity.
Keywords: Liver; metylace; Animals; Tumor Suppressor Protein p53; apoptóza; buněčné linie; Stem Cells; oxidační stres; játra; Cell Line, Tumor; Apoptosis; Cell Cycle; Oxidative Stress; receptory aromatických uhlovodíků; adukty DNA; proteinkinasy; Epithelial Cells; kmenové buňky; mutageny; Cell Line; buněčný cyklus; Methylation; regulace genové exprese; Receptors, Aryl Hydrocarbon; DNA Adducts; nádorový supresorový protein p53; krysa rodu Rattus; Protein Kinases; benzopyren; Mutagens; Gene Expression Regulation; zvířata; epitelové buňky; Rats; nádorové buněčné linie; Benzo(a)pyrene